Ekstraksi Senyawa Bioaktif dari Cladophora sp. Dengan Metode Solvent Free Microwave Assisted Extraction (SFMAE) - Yoni Rina Bintari; Helmin Elyani (JIMR - Journal of Islamic Medicine Research, 2017)
Introduction: Extraction stages is important, in order to discovery of bioactive compounds that have pharmalogical effects. Solvent Free Microwave Assisted Extraction (SFMAE) is alternative procedure with criteria of green chemistry and sustainability. Methods: In order the examine the effect of microwave power, six power level 0%, 20%, 40%, 60%, 80%, and 100% (0 W, 200 W, 400 W, 600 W, 800 W and 1000 W) were studied. The variation of adding water 10 ml/g, 15 ml/g, 20 ml/g and 30 ml/g were studied. Optimum condition of extraction from the highest yield. Phytochemichal screening using specific reagent to know bioactive compounds group.Results: The result obtained is the highest yield of 3,7333% with 400 W microwave power and 30 ml/g adding water in 360 seconds. The results of phytochemical screening of Cladophora Sp extract contain secondary metabolites of alkaloid, phenolic, terpenoid and saponin groups.Conclusion: From phytochemical screening, Cladophora sp. has potential of antioxidant and antibacterial activity, so the next research focus to antioxidant and antibacterial activity.Keywords: Extraction, SFMAE, Cladophora sp., Phytochemical